Budaya Flexing dan Tuntunan Al-Quran: Telaah Interpretasi QS. al-Dhuha 94:11 - Wulidal Habibi; Syukron Affani (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Social media has evolved into a means of self-actualization that has become a way to give and attract the attention of its users. Social media has become an open showcase for displaying personal spaces. To a certain extent, personal appearances on social media are no longer limited to displaying but also showing off with the aim of gaining attention, praise, and recognition, or what is popularly known as flexing. This paper focuses on exploring the negative and positive aspects of flexing culture in social media and the guidance on showing off in the Quran. The researcher will examine the relevance of flexing to QS. Aḍ-Ḍuha (94): 11 and analyze it using the double movement approach introduced by Fazlur Rahman. The result of the analysis is that in the Quran, showing off is only permissible for the purpose of expressing gratitude for Allah's blessings (tahadduts bi al-ni`mah) as in QS. al-Dhuha (94): 11. Any other purpose is considered behavior that is disliked by Allah, as exemplified in QS Luqman 31:18 and al-Hadid 57:20.